The impact of Chinese import penetration on Danish firms and workers - Ashournia, D; Munch, J; Nguyen, D (University of Oxford, 2014)
The impact of imports from low-wage countries on domestic labor market outcomes has been a hotly debated issue for decades. The recent surge in imports from China has reignited this debate. Since the 1980s several developed economies have experienced contemporaneous increases in the volume of imports and in the wage gap between high- and low-skilled workers. However, the literature has not been able to document a strong causal relationship between imports and the wage gap. Instead, past studies have attributed the widening wage gap to skill biased technological change. This paper finds evidence for the direct impact of low wage imports on the wage gap. Using detailed Danish panel data for firms and workers, it measures the effects of Chinese import penetration at the firm level on wages within job-spells and over the longer term taking transitions in the labor market into account. We find that greater exposure to Chinese imports corresponds to a negative firm-level demand shock, which is biased towards low-skill intensive products. Consistent with this an increase in Chinese import penetration results in lower wages for low skilled employees.